Psychoanalytic thinking in mental health settings - Evans, Marcus, 1961- (New York, NY : Routledge, 2021)
"This book demonstrates the use of psychoanalytic thinking in front line mental health settings and aims to make available an approach to working with emotional and mental disturbance to a wide range of clinicians within psychiatric and other mental health settings. Rooted in the author's extensive clinical experiences, the approach explored in this book applies psychoanalytic thinking and discusses this in relation to the mental health conditions regularly encountered in psychiatric settings, such as Schizophrenia, Manic Depression, Psychotic Depression, Anorexia, Deliberate Self Harm and Personality Disorder. The book therefore provides valuable and practical ways of working with these difficult, complex, and problematic conditions. It further makes sense of the relationships and emotions encountered when working in these settings and introduces possibilities for more effective and rewarding ways of working, including a model of support through supervision, reflective practice, and clinical discussion. Illustrated by clinical examples from more than four decades of experience in the field, this book is ideal for the interested mental health practitioner"--
Introduction -- Theory in Practice -- Supervision and Consultation: turning in to psychotic communications in frontline mental health settings -- Therapeutic and Anti-Therapeutic Factors in Therapeutic Relationships -- Psychoanalytic Understanding of Depressional and Suicidal Risk -- Psychotherapeutic work with Emotionally Unstable Personality Disorder -- Turning in to Psychotic Communication on a Psychiatric Intensive Care Unit -- Therapeutic work with treatment resistant patients -- The Contribution of Psychanalytic Perspectives on the patient's relationship with their bodies -- Social Systems and Social Defence.
OCLC-licensed vendor bibliographic record.
Keywords: Psychotherapy; Mental health personnel and patient; Psychoanalytic interpretation; Mental health services; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health